Pilot randomized controlled trial of a symptom cluster intervention in advanced cancer. Issue 1 (30th October 2018) - Wells‐Di Gregorio, Sharla M.; Marks, Donald R.; DeCola, Joseph; Peng, Juan; Probst, Danielle; Zaleta, Alexandra; Benson, Don; Cohn, David E.; Lustberg, Maryam; Carson, William E.; Magalang, Uly
Abstract: Objective: This study evaluated a three‐session acceptance‐based cognitive behavioral ‐acceptance and commitment therapy (CBT‐ACT) intervention targeting a common symptom cluster in advanced cancer—worry‐insomnia‐depression‐fatigue. Methods: Twenty‐eight patients with advanced cancer were randomly assigned to the CBT‐ACT intervention or waitlist. At preintervention, participants completed a psychodiagnostic interview, standardized questionnaires, and a sleep diary. Intervention and waitlist groups were reassessed after 6 weeks, at which point the waitlist group completed the intervention. Results: Participants receiving the intervention demonstrated improved sleep efficiency ( P  = 0.0062, d = 1.08), sleep latency ( P  = 0.028, d = −0.86), insomnia severity ( P  = 0.0047, d = −1.18), and worry ( P  = 0.026, d = −0.89) compared with waitlist controls. They also demonstrated a 7‐point reduction on depression ( P  = 0.03, d = −0.88), reduced hyperarousal ( P  = 0.005, d = −1.51), and a decrease in distress ( P  = 0.032, d = −0.83). Effects were maintained for the whole sample in sensitivity analyses. Effects on uncertainty intolerance approached significance ( P  = 0.058). No effect was found on fatigue. Conclusions: The CBT‐ACT group performed significantly better than the waitlist control group. CBT‐ACT yielded strong effects for worry, sleep, depression, emotional distress, total distress, and hyperarousal. Future studies will enhance the fatigue and uncertainty tolerance components of the intervention.